Mutation profile and immunoscore signature in thymic carcinomas: An exploratory study and review of the literature. Issue 9 (11th March 2021) - Asselta, Rosanna; Di Tommaso, Luca; Perrino, Matteo; Destro, Annarita; Giordano, Laura; Cardamone, Giulia; Rubino, Luca; Santoro, Armando; Duga, Stefano; Zucali, Paolo Andrea
Abstract: Background: Significant efforts have been made to investigate the molecular pathways involved in thymic carcinogenesis. However, genetic findings have still not impacted clinical practice. The aim of this exploratory trial was to evaluate the immunoscore and molecular profile of a series of thymic carcinomas (TCs), correlating this data with clinical outcome. Methods: Formalin‐fixed, paraffin‐embedded (FFPE) TC tissues were retrieved from our center archive. The immunoscore was evaluated according to Angell and Gallon. DNA was extracted from FFPE tumor samples and, when available, from adjacent histologically normal tissues. Next‐generation sequencing (NGS) was performed targeting hotspot regions of 50 oncogenes and tumor suppressor genes. Results: A series of 15 TCs were analyzed. After a median follow‐up of 82.4 months, the median overall survival was 104.7 months. The immunoscore was >2 in 5/15 patients (33%). Among the investigated genes, absence of mutations was observed in 5/15 patients (33%), whereas three variants in 1/15 (6%) patient, two variants in 4/15 (26%) patients, and one variant in 5/15 patients (33%) were found. The most recurrently mutated genes were FGFR3 (five mutations) and CDKN2A (three mutations, two of which were nonsense). Patients with CDKN2A loss showed a statistically significantly worse survival ( P = 0.0013), whereas patients with FGFR3 mutations showed a statistically significantly better survival ( P = 0.048). Conclusions: This study adds data to the few existing reports on the mutational landscape of TCs, providing the first comprehensive analysis to date. Here, we confirm the low rate of mutations in TCs and suggest FGFR3 and CDKN2A mutations as intriguing potential therapeutic targets. Abstract : Immunoscore, molecular profile, and their correlation with the clinical outcomes of a series of 15 thymic carcinomas were evaluated. We confirmed the low rate of mutations in thymic carcinomas and suggest FGFR3 and CDKN2A mutations as intriguing potential therapeutic targets